Russia's geopolitical predicament and the intellectual propositions of Alexander Dugin addressing it - PhD professor Sarmad Abdulsatar Amin; Hanin Jasim Ali (The college of law and political science journal, 2024)
Since his arrival to power in Russia, Vladimir Putin and the other decisionmakers has been planning for regaining the Russian international prestige. This vision has been guided by Russian thinkers who theorize the possibility of dealing with the geopolitical crises of the country after the collapse of the Soviet Union (SU) and the shifting to the unipolarity led by the United States (US). The vacuum of post-SU era resulted in regional and international competitions due to the strategic traits of the Eurasian region and its peripheries. This study aims to explore the causal relationship between place and politics.